Phytoalexin accumulation in the forage crop, M edicago sativa as defence against the soil-borne wilt pathogen Verticillium albo-atrum - J. M. MILTON, C. J. SMITH and (Indian Phytopathology, 2002)
Growth of the forage crop Medicago saliva is restricted due to the presence of the soil-borne pathogen V. albo-atrum. M. saliva shows resistance to some isolates of this fungus. The present study deals with the interaction between M. saliva and two isolates of the fungus of which one is pathogenic, the other one being non-pathogenic. Effects upon phytoalexin accumulation of elicitors prepared from cultures of the two isolates are described, and the effect on the activity of phenylalanine ammonia lyase has also been measured.